2000
DOI: 10.1152/physiolgenomics.2000.3.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of gene expression changes during acute and chronic exposure to Δ9-THC in rats

Abstract: Large-scale cDNA microarrays were employed to assess transient changes in gene expression levels following acute and chronic exposure to cannabinoids in rats. A total of 24,456 cDNA clones were randomly selected from a rat brain cDNA library, amplified by PCR, and arrayed at high density to investigate differential gene expression profiles following acute (24 h), intermediate (7 days), and chronic (21 days) exposure to Delta(9)-tetrahydrocannabinol (Delta(9)-THC), the psychoactive ingredient of marijuana. Hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 49 publications
2
56
2
Order By: Relevance
“…Previous studies have noted altered regulation of ubiquitin-conjugating enzyme 24 h after D 9 -THC administration (Kittler et al, 2000;Grigorenko et al, 2002) and the current study extends this to 17 days posttreatment. Expression of this protein may indicate disruption of cell proliferation and repair resulting from drug exposure during the adolescent period.…”
Section: Protein Expression Profiles In Adolescent Brainssupporting
confidence: 68%
See 3 more Smart Citations
“…Previous studies have noted altered regulation of ubiquitin-conjugating enzyme 24 h after D 9 -THC administration (Kittler et al, 2000;Grigorenko et al, 2002) and the current study extends this to 17 days posttreatment. Expression of this protein may indicate disruption of cell proliferation and repair resulting from drug exposure during the adolescent period.…”
Section: Protein Expression Profiles In Adolescent Brainssupporting
confidence: 68%
“…MBP is a major constituent of the myelin sheath that allows fast saltatory conduction of nerve pulses (Vanrobaeys et al, 2005). Previous studies employing microarray techniques have demonstrated downregulated MBP expression immediately after chronic D 9 -THC administration (Kittler et al, 2000;Grigorenko et al, 2002). Again, the current study is of interest as it shows such effects more than 2 weeks after D 9 -THC exposure, and only in rats exposed to D 9 -THC during the adolescent period.…”
Section: Protein Expression Profiles In Adolescent Brainsmentioning
confidence: 61%
See 2 more Smart Citations
“…G␤␥ may transduce cannabinoid signals to phosphatidylinositol (PI) 4 3-kinase and mitogen-activated protein kinases (6). Cannabinoid regulation of the CREB and NF-B are among the few transcriptional effects of cannabinoid exposure that have been documented in immune cell contexts (6,(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%